2011
DOI: 10.5573/jsts.2011.11.1.040
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Dimensional (2D) Analytical Model for the Potential Distribution and Threshold Voltage of Short-Channel Ion-Implanted GaAs MESFETs under Dark and Illuminated Conditions

Abstract: Abstract-A two-dimensional (2D) analytical model for the potential distribution and threshold voltage of short-channel ion-implanted GaAs MESFETs operating in the sub-threshold regime has been presented. A double-integrable Gaussian-like function has been assumed as the doping distribution profile in the vertical direction of the channel. The Schottky gate has been assumed to be semi-transparent through which optical radiation is coupled into the device. The 2D potential distribution in the channel of the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…often have a finite state interface density and the ideal device pinch. Certain physical parameters such as the barrier height, the density of the interface states, generate problems of the interface states, substrate compensation traps and non-homogeneous Schottky barrier, the model includes the voltage Vt and the Schottky potential contact at the same time given in (19). In submicron GaAs-MESFETs, in order to study the submicron MESFET, we have simulated and drawn the device current-voltage (I-V) characteristics for different drain and gate voltages for temperatures ranging from 200K to 600K steped by 100K.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…often have a finite state interface density and the ideal device pinch. Certain physical parameters such as the barrier height, the density of the interface states, generate problems of the interface states, substrate compensation traps and non-homogeneous Schottky barrier, the model includes the voltage Vt and the Schottky potential contact at the same time given in (19). In submicron GaAs-MESFETs, in order to study the submicron MESFET, we have simulated and drawn the device current-voltage (I-V) characteristics for different drain and gate voltages for temperatures ranging from 200K to 600K steped by 100K.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Several analytical models have been proposed, among his known model have found the model of Larson [10], the model of Curtice and Curtice-Ettenburg model [11], [12], the disadvantage of these models 1272 is that they cannot simulate the dependence of the parameter Vt on VDS and VGS, so they are not suitable for short-channel devices [12], [13], one of the problems of the Tajima et al [14] is that it does not take into account the simulation of Gm and Gd, for the simulation of MESFET-DC characteristics, Rodriguez introduced an expression based on an expansion of the Curtice model depending on the parameter Vt on the IDS expression [13], the adjustment of the precision of the Curtice model at the level of the linear and saturation regions is improved by the Chalmers model [15], let's look at the Dobes model [16] that we notice for n=2, we return to the Rodriguez model [17], the Materka-Kacprzak model [18] Seemed to be a bit more precise in the linear and saturation regions, but its accuracy degrades significantly when the device size is reduced [19], the Memon model simulates the characteristics of a MESFET-GaAs having a finite density of states at the Schottky barrier [20], by modifying the Ahmed model [17]. It has been shown that the Memon model can simulate the characteristics of the device [20], we therefore propose another new model which takes into account the interface states at the level of the Schottky barrier, which takes into account the simplicity of determining the different characteristics of the MESFET-GaAs device, such as the output transconductance, the output conductance of the MESFET device.…”
Section: Introductionmentioning
confidence: 99%
“…where V sat is the minimum drain-source voltage required for the onset of velocity saturation [28,38], v s is the saturation velocity, (v s = 2.3 × 10 5 m/s) [39], μ 0 is the low-field carrier mobility (μ 0 = 2800 cm 2 /V × s) [40] and V th is the short-channel threshold voltage of GaAs OPFETs [41]. It is important to mention here that for the drain-source voltage greater than V sat , the depletion region at drain end of the gate extends laterally into the channel thus reducing the effective channel length (as shown in Fig.…”
Section: I-v Characteristics In the Saturation Region Of Operationmentioning
confidence: 99%
“…The drain current expression [i.e. (20)] derived in the previous section is strictly valid up to the onset of saturation when the electric field in the channel reaches saturation electric field ( E c ) at Vds=Vsat=vs)(Vgs+VopVthvsL+μ0)(Vgs+VopVth where V sat is the minimum drain–source voltage required for the onset of velocity saturation [28, 38], v s is the saturation velocity, ( v s = 2.3 × 10 5 m/s) [39], μ 0 is the low‐field carrier mobility ( μ 0 = 2800 cm 2 /V × s) [40] and V th is the short‐channel threshold voltage of GaAs OPFETs [41]. It is important to mention here that for the drain–source voltage greater than V sat , the depletion region at drain end of the gate extends laterally into the channel thus reducing the effective channel length (as shown in Fig.…”
Section: Modelling Of Current (I)–voltage (V) Characteristicsmentioning
confidence: 99%
“…To determine the second term, we based for the works Wu (1992, 1993), Jit et al (2003Jit et al ( , 2011 and Morarka and Mishra. (2005), these studies are used the Green's functions and superposition techniques.…”
Section: D Analytical Modelmentioning
confidence: 99%